Comparison of staining of mitotic figures by haematoxylin and eosin-and crystal violet stains, in oral epithelial dysplasia and squamous cell carcinoma - Ankle Madhuri; Kale Alka; Charantimath Seema (Wolters Kluwer Medknow Publications, 2007)
Mitosis of cells gives rise to tissue integrity. Defects during mitosis bring about abnormalities. Excessive proliferation of cells due to increased mitosis is one such outcome, which is the hallmark in precancer and cancer. The localization of proliferating cells or their precursors may not be obvious and easy. Establishing an easy way to distinguish these mitotic cells will help in grading and understanding their biological potential. Although immunohistochemistry is an advanced method in use, the cost and time factor makes it less feasible for many laboratories. Selective histochemical stains like toluidine blue, giemsa and crystal violet have been used in tissues including the developing brain, neural tissue and skin. Aim of the study: 1)To compare the staining of mitotic cells in haematoxylin and eosin with that in crystal violet. 2)To compare the number of mitotic figures present in normal oral mucosa, epithelial dysplasia and oral squamous cell carcinoma in crystal violet-stained sections with that in H and E-stained sections. Materials and Methods: Ten tissues of normal oral mucosa and 15 tissues each of oral epithelial dysplasia seen in tobacco-associated leukoplakia and squamous cell carcinoma were studied to evaluate the selectivity of 1% crystal violet for mitotic figures. The staining was compared with standard H and E staining. Statistical analysis was done using Man-Whitney U test. Results: A statistically significant increase in the mean mitotic count was observed in crystal violet-stained sections of epithelial dysplasia as compared to the H and E-stained sections ( p = 0.0327). A similar increase in the mitotic counts was noted in crystal violet-stained sections of oral squamous cell carcinoma as compared to the H and E-stained sections.( p = 0.0443). No significant difference was found in the mitotic counts determined in dysplasia or carcinoma by either the crystal violet ( p = 0.4429) or the H and E-staining techniques ( p = 0.2717). Conclusion: One per cent crystal violet provides a definite advantage over the H and E-stained sections in selectively staining the mitotic figures.